Coalition Governance or Collusion Catastrophe: A Critical Examination of the 'Government of National Unity' in South Africa - Lehlohonolo Josiaya Malope; France Khutso Lavhelani Kgobe (NEGREI: Academic Journal of Law and Governance, 2026)
Coalition governance has emerged as a defining feature of fragmented democracies, raising critical questions about its implications for public administration performance. In South Africa, the establishment of a Government of National Unity (GNU) following the 2024 elections represents a significant departure from decades of dominant-party rule and presents a unique opportunity to examine how power-sharing arrangements affect administrative coherence and service delivery. Drawing on the literature on consociational democracy and governance capacity, this study employs qualitative document analysis and thematic analysis to examine the administrative dynamics of coalition governance under the GNU. The findings reveal that while coalition arrangements promote political inclusion, they also generate fragmented executive authority, intensified politicisation of administrative processes, weak conflict-resolution mechanisms, and adverse consequences for service delivery and public trust. These outcomes highlight a critical limitation of consociational democracy: its insufficient attention to administrative performance. Through an integration of power-sharing theory with perspectives on governance capacity, the study contributes to public administration scholarship by shifting the focus from coalition politics to coalition administration. The article argues that coalition governments require explicit administrative design features, such as clear authority structures and institutionalised coordination mechanisms, to translate political inclusion into effective governance. The findings offer broader lessons for coalition governance in fragmented democracies beyond South Africa.